DOP88 Thiopurine and allopurinol combination therapy and the risk of adverse outcomes and step-up medical therapy in inflammatory bowel disease patients: a nationwide Danish cohort study. (25th January 2019) - Thomsen, S B; Allin, K H; Burisch, J; Jensen, C B; Hansen, S; Gluud, L L; Theede, K; Kiszka-Kanowitz, M; Nielsen, A M; Jess, T
Abstract: Background: Thiopurine and allopurinol combination therapy is associated with clinical remission in patients with inflammatory bowel diseases (IBDs), but its influence on adverse outcomes, ie, IBD-related surgery, IBD-related hospitalisation, and death, and need for biological treatment is unclear. We compared these outcomes in patients with IBD treated with thiopurine and allopurinol and patients with IBD treated with thiopurine monotherapy. Methods: We established a nationwide cohort of patients with an IBD diagnosis who had been prescribed thiopurine therapy, 1999–2014, using Danish registry data. The primary outcome was a composite of any adverse outcome or need for biological treatment: IBD-related hospitalisation, IBD-related surgery, biological therapy initiation, or death, whichever came first. Poisson regression analyses were used to calculate incidence rate ratios (IRR) with 95% confidence intervals (CI) comparing patients exposed to allopurinol-co-therapy and patients exposed to thiopurine monotherapy. Exposure was analysed as a time-varying variable and IRRs were adjusted for IBD subtype, sex, age at treatment, calendar year, and age at diagnosis. Results: There were 10367 patients with IBD (Crohn's disease [CD] n = 5484, ulcerative colitis [UC] n = 4883) who were prescribed thiopurines, and of these 217 were exposed to allopurinol co-therapy. We observed 40 incident outcomes in patients exposed to allopurinol co-therapy among 129 person-years (PY) (IR = 310.1 per 1000 PY). In patients exposed to thiopurine monotherapy, we observed 4745 outcomes among 24585 PY (IR = 193.0 per 1000 PY). The adjusted IRR of an adverse outcome was not significantly different in the two groups of patients (IRR 1.26 [95% CI 0.92, 1.73]). The results did not differ when analysed in strata by IBD subtype (IRR = 1.25 (95% CI 0.78, 2.02) for CD, IRR = 1.23 [95% CI 0.82, 1.86] for UC). Conclusions: Thiopurine and allopurinol exposed IBD patients did not have a statistically significant different risk of surgery, hospitalisation, biological therapy initiation, and death, when compared with IBD patients exposed to thiopurine monotherapy. Even though allopurinol co-therapy seems to improve clinical remission in IBD patients in previous studies, our study does not suggest an association with subsequent clinical outcomes.